ANALISIS PERBANDINGAN KINERJA KEUANGAN PELAKU EKONOMI KREATIF (Studi Kasus Pada Distro Club dan BSM Distro di Kota Malang) - Hani’ah Fifrika Cinci; Jeni Susyanti; M. Agus Salim (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACT            This study aims to find out which financial performance is better between Distro Club creative economic actors and creative economic actors BSM Distro in Malang. The data used are primary data by collecting data through interviews. The tool used to analyze the financial performance of creative economic actors is using financial ratio analysis. The analysis shows that the financial performance of BSM Distro creative economic actors is better than the financial performance of Distro Club creative economic players in terms of profitability ratios and solvency ratios, while in terms of liquidity ratios the results show that Distro Club has better financial performance than BSM Distro.Keywords: Actors of Creative Economy, Ratio Analysis and Financial Performance